Seismic Dispersion, Attenuation, and Frequency-Dependent Anisotropy of Fractured Reservoirs - Guo, Junxin (Curtin University, 2018)
Seismic characterization of fractures is of great importance for the oil and gas production. For this purpose, in this thesis, I explore the mechanisms for the seismic dispersion, attenuation, and frequency-dependent anisotropy in fractured reservoirs. Two important mechanisms are investigated, one is the wave-induced fluid flow (WIFF) and the other is the wave scattering by fractures. This study provides numerically validated theoretical models, which lays the basis for developing seismic attributes for fractured reservoir characterization.